Socialization is Important to Grow Social Sense and Empathy for People in Berkat Bintang Sejati Orphanages - Feby Yoana Siregar; Merry Rusida S; Devi Alvionita Alindra; Wenny; Ivana; Kiki Goslim; Munthe, Herlin (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
Community Service Activities are carried out on Jl Sei Sihalian, Sei Sikambing D, Kec. Medan Petisah, Medan City, North Sumatra 20114. Time for implementation activities January 28 2024. Service activities carried out in the form of discussions and direct practice with children at the Berkat Bintang Sejati Orphanage. In helping children overcome their problems and find alternatives to fulfill their living needs and have the skills to provide them with life. In this program children are expected to be able to live independently and develop every potential they have so that the child's welfare can be fulfilled and the child's normal development can be fulfilled and it is hoped that the child will be able to develop the abilities he has, because in a child's development it is hoped that all the child's needs can be met, so that development children become optimal.